2021
DOI: 10.3390/pathogens10070800
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping Cryptosporidium xiaoi, a Common Pathogen in Sheep and Goats

Abstract: Cryptosporidiosis is a significant cause of diarrhea in sheep and goats. Among the over 40 established species of Cryptosporidium, Cryptosporidium xiaoi is one of the dominant species infecting ovine and caprine animals. The lack of subtyping tools makes it impossible to examine the transmission of this pathogen. In the present study, we identified and characterized the 60-kDa glycoprotein (gp60) gene by sequencing the genome of C. xiaoi. The GP60 protein of C. xiaoi had a signal peptide, a furin cleavage site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Thus, no obvious differences were observed in the distribution of C. bovis gp60 subtype by host. This was different from the observations in other Cryptosporidium species, including the genetically related C. xiaoi and C. ryanae [18,22,36].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, no obvious differences were observed in the distribution of C. bovis gp60 subtype by host. This was different from the observations in other Cryptosporidium species, including the genetically related C. xiaoi and C. ryanae [18,22,36].…”
Section: Discussioncontrasting
confidence: 99%
“…The high prevalence and long duration of C. bovis infection and frequent occurrence of multiple subtype families on a single farm could greatly facilitate the occurrence of genetic recombination among isolates, leading to the emergence of new subtypes. This was in agreement with the observations in C. xiaoi and C. ryanae [18,22]. Several studies on other Cryptosporidium species also indicated the frequent genetic recombination at the gp60 locus [34,35].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, C. hominis subtype IfA19G1R5 has 19 TCA (A) repeats, 1 TCG repeat (G) repeat and 5 AAGAAGGCAAAGAAG repeats (R). For some divergent species and genotypes, including C. ubiquitum, C. felis, C. canis, C. ryanae, C. xiaoi, C. bovis and Cryptosporidium chipmunk genotype I and skunk genotype, whole-genome sequencing (WGS) has been required to identify the gp60 loci in order to develop typing systems [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The trinucleotide repeats (TCA, TCG, TCT) are absent from gp60 genes in C. ubiquitum, C. felis, C. canis, C. ryanae, C. bovis and C. xiaoi [ 44 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%